Tourism progress in the SADC region Postcolonial era milestones - Zhou, Zibanai (Taylor and Francis, 2021)
This chapter addresses an under-representation in the current tourism discourse of the developmental strides made within the SADC region’s tourism landscape over the last few decades. A new Pan-African narrative is proffered, outlining landmark tourism developments registered in the postcolonial era. The SADC block is strengthening its strategy to leverage the international tourism market’s appetite for the region’s rich tourist attractions base. For the analysis, data were gleaned from policy documents, expert opinions, surveys and the author’s anecdotal experience. Results confirm largely positive efforts towards reconfiguration of the SADC region’s tourism industry in the spheres of product development (e.g. through Peace Parks); destination connectivity (by liberalising the aerospace and actualisation of a uni-visa system); expansive human resource skills development; a well-knitted tourism supportive infrastructural backbone; sharpened customer oriented marketing and promotional approaches; and the region’s positioning as a renowned meetings, incentives, conventions and exhibitions (MICE) destination. Granting that challenges remain, the SADC region’s tourism sector is poised for growth, buoyed by the upward trend in per capita income and ease to do business.